Clinical and radiological outcomes of a cervical cage with integrated fixation. Issue 3 (January 2019) - Lonjon, Nicolas; Favreul, Emmanuel; Huppert, Jean; Lioret, Eric; Delhaye, Manuel; Mraidi, Ramzi
Abstract : Abstract: Cervical cages with integrated fixation have been increasingly used in anterior cervical discectomy and fusion (ACDF) to avoid complications associated with anterior cervical plates. The purpose of this paper is to provide 2-year follow-up results of a prospective study after implantation of a cervical cage with an integrated fixation system. This was a prospective multicenter outcome study of 90 patients who underwent ACDF with a cage with integrated fixation. Fusion was evaluated from computed tomography images (CT-images) by an independent laboratory at 2-year follow-up (FU). Clinical and radiological findings were recorded preoperatively and at FU visits and complications were reported. At 24 months, the fusion rate was 93.4%. All average clinical outcomes were significantly improved at 2 years FU compared to baseline: neck disability index (NDI) 18.9% vs 44.4%, visual analog scale (VAS) for arm pain 18.2 mm vs 61.9 mm, VAS for neck pain 23.9 mm vs 55.6 mm. Short form-36 (SF-36) scores were significantly improved. One case of dysphagia, which resolved within 12 months, and 1 reoperation for symptomatic pseudarthrosis were reported. Subsidence with no clinical consequence or reoperation was reported for 5/125 of the implanted cages (4%). There was also 1 case of per-operative vertebral body fracture that did not require additional surgery. Superior and inferior adjacent discs showed no significant change of motion at 2-year FU compared to baseline. Disc height index (DHI) and lordosis were enhanced and these improvements were maintained at 1 year. The ACDF using cages with an integrated fixation system demonstrated reliable clinical and radiological outcomes and a high interbody fusion rate. This rate is comparable to the rate reported in recent series using other implants with integrated fixation, but the present device had a lower complication rate.